Probiotic for Prevention and Treatment of Necrotizing Enterocolitis in Preterm Infant - Risma Nopara Sigmahadewi (Eduvest - Journal of Universal Studies, 2024)
Necrotizing enterocolitis (NEC) is a serious condition that is often experienced by premature babies. NEC can cause inflammation and tissue death in the baby's intestines, potentially leading to life-threatening complications. Therefore, it is necessary to prevent NEC in premature babies, one of which is with probiotics. This study aims to review existing literature regarding the effectiveness of probiotics in the prevention and treatment of NEC in premature infants. This research employs a systematic literature review method. Data collection was conducted by searching for literature in the Google Scholar and PubMed databases. The data analysis was performed using qualitative methods. The research results show that probiotics are therapeutic agents that can be used as an effort to prevent and treat NEC in premature babies. Several studies show that giving probiotics to premature babies can reduce the risk of developing NEC. The most effective probiotic strain is Lactobacillus rhamnosus or combined with Bifidobacterium infantis.